Ecuador Trade and Investment Competitiveness Report - World Bank Group (World Bank, Washington, DC, 2019)
The internationalization of the Ecuadorian economy is necessary if the country is to successfully adopt a development model led by the private-sector. The Ecuadorian government is seeking to accelerate growth and sustain social progress by giving greater prominence to the private sector; it does at a time when external conditions are less favorable than at any time in the last decade. This report has three main objectives; to provide a systematic benchmark of Ecuador’s connection to the global economy, to identify key bottlenecks, and to make recommendations for enhancing the competitiveness of the private sector. The assessment is broken down into two sections. First, there is a section about international competitiveness outcomes, which assess Ecuador’s performance and identifies the challenges associated with connecting to international markets. The analysis looks at outcomes throughout the four competitiveness channels; that is, exports, imports, foreign direct investment (FDI), and global value chains (GVCs). The report’s second main section contains a competitiveness diagnostic about the key drivers behind the previously identified challenges and provides actionable policy recommendations to overcome them. The determinants are grouped in four mutually exclusive groups: (i) the macro and fiscal framework; (ii) the institutional and regulatory framework governing trade and investment; (iii) supply-side factors; and (iv) demand-side factors.